Odpowiedź :
Odpowiedź:
zad 1
a) [tex]x^{2} -9=0[/tex]
[tex](x-3)(x+3)=0[/tex] ze wzoru skróconego mnożenia
[tex]x-3=0[/tex] v [tex]x+3=0[/tex]
[tex]x=3[/tex] v [tex]x=-3[/tex]
b) [tex]16 - 4 x^{2} =0[/tex]
[tex](4-2x)(4+2x)=0[/tex]
[tex]4-2x=0[/tex] v [tex]4+2x=0[/tex]
[tex]-2x=-4/:(-2)[/tex] v [tex]2x=-4/:2[/tex]
[tex]x=2[/tex] v [tex]x=-2[/tex]
zad 2
a) [tex]4x^{2} -8x=0[/tex]
[tex]4x(x-2)=0[/tex]
[tex]4x=0[/tex] v [tex]x-2=0[/tex]
[tex]x=0[/tex] v [tex]x=2[/tex]
b) [tex]3x+12x^{2} =0[/tex]
[tex]3x(1+4x)=0[/tex]
[tex]3x=0[/tex] v [tex]1+4x=0[/tex]
[tex]x=0[/tex] v [tex]4x=-1[/tex]
[tex]x=-0,25[/tex]